Development of Digital Business Literacy in Farming Management in Makassar City - Amalia Amalia; Thamrin Tahir; Muhammad Hasan; Nurdiana Nurdiana; Tuti Supatminingsih (Cita Konsultindo Research Center, 2022)
ABSTRACT This research was conducted with the aim of knowing the development of digital business literacy activities in farming management in Makassar City which was carried out by Anggrek KWT. This study was conducted in Bara-baraya sub-district, Makassar City. The development of digital business literacy is very suitable to be researched to measure the extent to which the development is carried out by the Anggrek KWT farming business. The research method used in this study is using qualitative research methods with descriptive use. This study uses data collection techniques through field observations and interview methods. There were 4 informants in this study, namely the chairman, secretary, treasurer, and also the father of the field extension worker at Anggrek KWT. Informant sampling was used using purposive sampling technique. This study suggests that there is a lack of digital business literacy development carried out by members of Anggrek KWT. Digital business literacy is only carried out if there are training activities by the instructor and not carried out routinely. The development that needs to be done is more related to digital business literacy activities, namely (1) utilizing technology (2) conducting routine socialization related to digital business (3) overcoming obstacles by adding facilities to support literacy activities. Keywords: digital business literacy, urban farming